Evaluasi Program Pembelajaran Ilmu Pengetahuan Alam (IPA) Pada Adi Widya Pasraman Di Provinsi Bali Dengan Model Evaluasi Context Input Process Product (CIPP) - I Made Wiguna Yasa; I Komang Wisnu Budi Wijaya; Ni Kadek Supadmini; I Made Putra Aryana; Nina D Hana (Jayapangus Press, 2023)
Science learning is one of the subjects included in the curriculum of Pasraman including Adi Widya Pasraman. However, so far, there has been no research aimed at evaluating science learning in Pasraman. In addition, the results of science literacy surveys in Indonesia recently have experienced a decline, so science learning needs to be evaluated. This research aimed to: 1) evaluate the science learning program at Adi Widya Pasraman in Bali Province using the Context, Input, Process and Product (CIPP) model and 2) analyze the effectiveness of the science learning program at Adi Widya Pasraman in Bali Province. This research was classified as an evaluative research study. The population and sample for this research were all Adi Widya Pasraman in Bali province. The instrument of this research was a questionnaire as the main instrument and was reinforced with observation sheets and interview guidelines. The data was analyzed descriptively and the effectiveness test was carried out using the Glickmann model. The research results showed that: 1) the aspects of context and process t are effective and good criteria; 2) the aspects of input and product are classified as sufficient and less effective; 3) overall the science learning program at Adi Widya Pasraman in Bali Province is quite effective.